2021
DOI: 10.3390/nu13103484
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Improves Cardiac-Renal Dysfunction Caused by Hypertrophy through Calcineurin-NFATc3 Signaling

Abstract: Cardiac hypertrophy can lead to congestive heart failure and is a leading cause of morbidity and mortality worldwide. In recent years, it has been essential to find the treatment and prevention of cardiac hypertrophy. Betulinic acid (BA), the main active ingredient in many natural products, is known to have various physiological effects. However, as the potential effect of BA on cardiac hypertrophy and consequent renal dysfunction is unknown, we investigated the effect of BA on isoprenaline (ISO)-induced cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Creatine kinase (CK) is mainly used in the diagnosis of myocardial infarction, which is widely in skeletal muscle, cardiac muscle, and brain tissue. Serum atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) activities are used to diagnose and monitor the course and efficacy of heart failure [ 18 ]. CK, ANP, and BNP levels were considerably greater in the DM group than in the CTL group ( P < 0.01); SMY and Met lowered CK, ANP, and BNP levels ( P < 0.05, P < 0.01) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Creatine kinase (CK) is mainly used in the diagnosis of myocardial infarction, which is widely in skeletal muscle, cardiac muscle, and brain tissue. Serum atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) activities are used to diagnose and monitor the course and efficacy of heart failure [ 18 ]. CK, ANP, and BNP levels were considerably greater in the DM group than in the CTL group ( P < 0.01); SMY and Met lowered CK, ANP, and BNP levels ( P < 0.05, P < 0.01) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…CaN is a serine/threonine protein phosphatase. After activation by the upstream Ca 2+ -calmodulin complex, CaN dephosphorylates the p-NFAT protein and then promotes the nuclear localization of NFAT [ 37 ]. After being combined with GATA-4, the NFAT/GATA-4 complex stimulates hypertrophy-related fetal gene expression [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of oxidative stress can damage the membrane lipids of cardiomyocytes, destroy the function and integrity of cardiomyocytes, trigger myocardial cell apoptosis and death and ultimately lead to cardiomyocyte loss and heart disease. Some studies have shown that the protective effect of betulinic acid on I/R- or H/R-induced cardiomyocytes might be related to its upregulation of antioxidative ability [ 23 ]. In this study, we observed that BTA07 reduced the level of MDA, significantly increased levels of SOD and GSH-Px and regulated the activation of caspase-3 in the isolated rat heart during the process of I/R injury in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%